2000
DOI: 10.1002/(sici)1097-0320(20000215)42:1<18::aid-cyto4>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Improving accuracy in the grading of renal cell carcinoma by combining the quantitative description of chromatin pattern with the quantitative determination of cell kinetic parameters

Abstract: The determination of grade and stage in renal cell carcinomas (RCCs) often fails to predict the actual clinical outcome for individual patients. The aim of the present work was to investigate whether it is possible to significantly improve the prognostic accuracy of the grading system by using the combination of two independent computer‐assisted microscopy techniques. The first technique relates to the quantitative description of morphonuclear and nuclear DNA content features by means of the image analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…There is much data indicating that a high level of cell division, measured by rapid incorporation of labeled DNA precursors (33) or the activation of cell cycle proteins (34), is correlated within a particular tumor type with a poor survival. In addition, studies of the expression of genes involved in protein synthesis suggest that a high level of protein synthesis is also associated with poor prognosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…There is much data indicating that a high level of cell division, measured by rapid incorporation of labeled DNA precursors (33) or the activation of cell cycle proteins (34), is correlated within a particular tumor type with a poor survival. In addition, studies of the expression of genes involved in protein synthesis suggest that a high level of protein synthesis is also associated with poor prognosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Yasunaga et al [42] showed the AgNOR score to be an independent prognostic factor associated with survival; however, other studies did not find this to be so [43]. Francois et al [44] demonstrated how it may also be useful in improving conventional renal cell grading systems.…”
Section: Nuclear Parametersmentioning
confidence: 99%
“…Choi et al extended the morphological analysis to three-dimensional nuclei and applied their system to RCC grading [9]. In addition to morphological features, Francois et al used cell kinetic features in their RCC grading system [10]. Finally, Raza et al used a scale invariant feature transform (SIFT) method to classify RCC subtypes [11].…”
Section: Introductionmentioning
confidence: 99%